Assessing the Functional Role of Frontal Eye Fields in Voluntary and Reflexive Saccades Using Continuous Theta Burst Stimulation - Gurel, Seref Can; Castelo-Branco, Miguel; Sack, Alexander T.; Duecker, Felix (Frontiers in Neuroscience, 2018)
The frontal eye fields (FEFs) are core nodes of the oculomotor system contributing to saccade planning, control, and execution. Here, we aimed to reveal hemispheric asymmetries between left and right FEF in both voluntary and reflexive saccades towards horizontal and vertical targets. To this end, we applied fMRI-guided continuous theta burst stimulation (cTBS) over either left or right FEF and assessed the consequences of this disruption on saccade latencies. Using a fully counterbalanced within-subject design, we measured saccade latencies before and after the application of cTBS in eighteen healthy volunteers. In general, saccade latencies on both tasks were susceptible to our experimental manipulations, that is, voluntary saccades were slower than reflexive saccades, and downward saccades were slower than upward saccades. Contrary to our expectations, we failed to reveal any TMS-related effects on saccade latencies, and Bayesian analyses provided strong support in favor of a TMS null result for both tasks. Keeping in mind the interpretative challenges of null results, we discuss possible explanations for this absence of behavioral TMS effects, focusing on methodological differences compared to previous studies (task parameters and online versus offline TMS interventions). We also speculate about what our results might reveal about the functional role of FEF.